O estado da arte em referenciais geodésicos: ITRF2000 e as próximas realizações do ITRS - Monico, João Francisco Galera; Soto, Juan Carlos Báez; Drewes, Hermann (My University, 2005)
In this paper is presented a brief historic of the ITRS realizations, giving details of the most recent, ITRF2000, as well as the parameters involved in the transformation among them. Some deficiencies of ITRF2000 are presented together with descriptions of how should be it in the future. Therefore, the status of Geodetic Reference System will be presented. Quality control analysis for some of the stations situated in the South American continent is presented in terms of precision and discrepancies with respect to other frames. Finally, it was emphasized about the care that one should take when using coordinates of stations located in regions subjected to seismic shock and earthquakes.
Status of the art on geodetic reference frame: ITRF2000 and the next ITRS realizations